2020
DOI: 10.56829/2158-396x-20.2.38
|View full text |Cite
|
Sign up to set email alerts
|

Special Education Teachers’ Preparedness for Teaching Emergent Bilingual Students with Disabilities

Abstract: Throughout the United States, public school districts serve increasing numbers of students with disabilities who are in the process of developing proficiency in English as a new or additional language. As a result, the need persists for special education teacher preparation programs to cultivate competencies for meeting the needs of emergent bilingual students with disabilities. In this study, researchers gathered special education teachers’ perceptions of their current levels of competence for teaching emerge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…They felt effective when they knew the students' native language(s). This study corroborates with other research that demonstrates the importance of teachers' ability to leverage the multiplicity of students' languages into their instruction and assessment (Artiles and Ortiz, 2002;Jozwik et al, 2020;Ortiz et al, 2020). Miranda et al (2019) examined a special education teacher education program that had revised their curriculum to support the education of EBs with disabilities and found the content about EBs to be disjointed and teachers' sense of efficacy in teaching EBs to be lacking.…”
Section: Monolingual English Presumptions In Educational Programming ...supporting
confidence: 86%
“…They felt effective when they knew the students' native language(s). This study corroborates with other research that demonstrates the importance of teachers' ability to leverage the multiplicity of students' languages into their instruction and assessment (Artiles and Ortiz, 2002;Jozwik et al, 2020;Ortiz et al, 2020). Miranda et al (2019) examined a special education teacher education program that had revised their curriculum to support the education of EBs with disabilities and found the content about EBs to be disjointed and teachers' sense of efficacy in teaching EBs to be lacking.…”
Section: Monolingual English Presumptions In Educational Programming ...supporting
confidence: 86%
“…Consistent with the findings of Robb et al [5], only two out of the four participants reported having any prior training in working with ELL students. Like Jozwik et al [9] found, the participants' responses suggested a limited confidence in their abilities to work with students in the ELL population prior to the experience. Participants reported that they gained both experience and confidence in working with this population, with one noting that it is likely that they may have a student who is dually identified on their caseload.…”
Section: Discussionmentioning
confidence: 51%
“…Moreover, recent research continues to confirm these findings. Jozwik et al [9] found that both preservice and in-service teachers self-assessed their competence in educating bilingual students as not proficient. In a program review of one institution's special educator training program, Miranda et al [10] reported that, while a curriculum pertaining to the education of ELL students with disabilities was included, this curriculum was "scattered and disjointed".…”
Section: Limited Competencementioning
confidence: 99%
See 1 more Smart Citation